THE SYMBOLIC MEANING OF WAYANG IN JAVANESE COMMUNITY TRANSMISSION AND ISLAMIC EDUCATION SUFISM - Muhtar Sofwan Hidayat; Robingun Suyud El Syam; Mahmudi Mahmudi (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2024)
UNESCO has determined that wayang is a masterpiece of human oral and intangible cultural heritage, but there are those who understand that it is prohibited in Islamic teachings and should be abandoned. On the other hand, wayang fans are increasingly being abandoned due to poor understanding of the nature of wayang, so this article attempts to explain wayang in terms of its significance for Javanese society and the Sufism of Islamic education. Qualitative descriptive is the setting of this research, with inductive analysis. With a theoretical review, it is concluded: Wayang is a reflection of the reality of human life through a reflection of the essence of the noble culture of Javanese society. In Islamic educational Sufism, wayang depicts human life, where everything cannot be separated from the regulation and supervision of the Mastermind of life, namely Allah. So Walisongo uses it as a means of education adapted to Islamic teachings. Research recommends the symbolic meaning of wayang in the transmission of Javanese society and Sufism. Islamic education contributes to Islamic civilization and culture and Islamic education.